Electrolyte and secondary battery
By using electrolyte salts, initiators and solvent mixtures to form gel electrolytes in the battery, the problem of liquid electrolyte combustion and boiling at high energy density is solved, the safety and stability of the battery is improved, and the electrochemical characteristics are maintained.
Patent Information
- Application Number
- CN202411243591.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-20
AI Technical Summary
The liquid electrolytes in existing batteries have problems of combustion and local boiling under high energy density systems, which affect the stability and safety of the battery.
An electrolyte solution is provided, including an electrolyte salt, an initiator and a solvent mixture. The first solvent undergoes polymerization reaction with the initiator at a threshold temperature to form a gel electrolyte, reducing the risk of heat generation and short circuit, the second solvent improves flame retardant performance, and Keep liquid at operating temperature.
Effectively reduce the heat generated by the battery short circuit, improve the safety and stability of the battery, while maintaining the electrochemical characteristics of the liquid electrolyte, and enhancing the cycle life and high-temperature performance of the battery.
Smart Images

Figure CN119170870A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, in particular to the field of battery electrolyte technology, and specifically to an electrolyte and a secondary battery. Background Art
[0002] With the rapid development of the new energy vehicle industry, people's demand for high-energy density batteries is increasing, and at the same time, higher requirements are placed on the intrinsic safety characteristics of batteries as key components of new energy vehicles.
[0003] The liquid electrolyte in the battery, i.e. the electrolyte, still has certain safety issues in a high energy density system. On the one hand, the proportion of flammable solvents in the electrolyte is too large, and the electrolyte is very easy to burn and catch fire when the electrolyte temperature reaches a certain level; on the other hand, the electrolyte includes solvents with low boiling points and are sensitive to high temperatures. When the temperature rises, the electrolyte boils locally, affecting the overall stability and safety of the battery. Related technologies have proposed safe electrolytes, polymer gel electrolytes, and all-solid electrolytes. Safe electrolytes only delay the combustion of batteries to a certain extent. The polymer gel system has limited flame retardant properties and poor rate performance and low-temperature performance. There are many problems with the solid-solid interface of all-solid electrolytes.
[0004] Therefore, an electrolyte and a secondary battery are desired that can overcome at least one of the above problems. Summary of the invention
[0005] The present application provides an electrolyte and a secondary battery. The technical solution of the present application is as follows:
[0006] On the one hand, an electrolyte is provided, the electrolyte comprising an electrolyte salt, an initiator, and a solvent mixture. The electrolyte salt is dissolved in the solvent mixture; the solvent mixture comprises a first solvent and a second solvent. The first solvent is at least configured to undergo a polymerization reaction under the action of the initiator when the temperature of the electrolyte is greater than or equal to a threshold temperature. The second solvent is at least configured to improve the flame retardant properties of the electrolyte. The mass proportion of the solvent mixture in the electrolyte is in the range of 70%-80%, and the mass proportion of the first solvent in the solvent mixture is greater than or equal to 15% and less than or equal to 35%.
[0007] When the electrolyte temperature is greater than or equal to the threshold temperature, the first solvent and the initiator undergo a polymerization reaction to form a gel electrolyte, which can reduce the heat generated by the reaction of the electrolyte with the positive and negative electrodes, inhibit short circuits, isolate the electronic conduction between the positive and negative electrodes, and reduce the heat generated by the battery short circuit.
[0008] In addition, at operating temperature, the electrolyte remains liquid and has the electrochemical properties of conventional liquid electrolytes.
[0009] In a possible embodiment, the threshold temperature is greater than or equal to 80 degrees Celsius.
[0010] The threshold temperature is set to be greater than or equal to 80 degrees Celsius, which not only ensures the operating temperature of the electrolyte, but also avoids the boiling of other solvents when the temperature is too high and the first solvent and initiator have not yet polymerized, affecting the polymerization reaction and thus affecting the safety characteristics.
[0011] In a possible embodiment, the first solvent includes a compound containing an alkenyl group.
[0012] In a possible embodiment, the first solvent includes at least one of vinylene carbonate and vinyl ethylene carbonate.
[0013] Vinylene carbonate and vinyl ethylene carbonate have high relative dielectric constants, and the electrolyte obtained has high conductivity. In addition, vinylene carbonate has no side reaction at the interface between the positive and negative electrodes, and can inhibit the heat generation of the reaction there.
[0014] In a possible embodiment, the initiator includes at least one of an azo compound and a peroxide.
[0015] In a possible embodiment, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, di-tert-butyl peroxide and tert-butyl perbenzoate.
[0016] In a possible embodiment, the mass proportion of the initiator in the electrolyte is in the range of 0.1%-1%.
[0017] By adjusting the ratio, amount and / or type of the initiator, the temperature at which the polymerization reaction between the first solvent and the initiator occurs can be changed, that is, the threshold temperature of the electrolyte can be flexibly adjusted according to actual needs.
[0018] In a possible embodiment, the mass proportion of the second solvent in the solvent mixture is greater than or equal to 10% and less than or equal to 30%; and the second solvent includes at least one of a fluorinated solvent and a phosphate ester solvent.
[0019] In a possible embodiment, the second solvent includes at least one of methyl trifluoroethyl carbonate (FEMC), di(2,2,2-trifluoroethyl) carbonate (TFEC), trimethyl phosphate (TMP), triethyl phosphate (TEP), tri(2,2,2-trifluoroethyl) phosphate (TFP), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (D2), methyl perfluorobutyl ether (MFE), and 1,1,1,3,3,3-hexafluoroisopropyl methyl ether (HFPM).
[0020] The second solvent does not participate in the solvation of the electrolyte salt, and thus can increase the coupling probability of lithium ions with vinylene carbonate and / or vinyl ethylene carbonate, thereby increasing the dissociation ratio of the electrolyte salt.
[0021] In addition, methyl trifluoroethyl carbonate FEMC, di(2,2,2-trifluoroethyl) carbonate TFEC, and DEC have flame retardant and self-extinguishing properties, which can prevent the electrolyte from burning and catching fire during the thermal runaway stage.
[0022] In a possible embodiment, the electrolyte salt accounts for 10%-18% by mass in the electrolyte.
[0023] In a possible embodiment, the electrolyte salt includes at least one of lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium bis(trifluoromethylsulfonyl imide) and lithium bis(fluorosulfonyl imide).
[0024] In a possible embodiment, the concentration of the electrolyte salt in the electrolyte solution is in the range of 0.8 mol / L to 2 mol / L.
[0025] High-stability electrolyte salts have good chemical stability and thermal stability, which can increase the battery cycle life and maintain good performance at high and low temperatures. The property of not being easily decomposed at high temperatures can effectively reduce the risk of thermal runaway of the battery.
[0026] Most high-stability lithium salts, such as lithium bis(fluorosulfonyl)imide, have high ionic conductivity, which helps improve the charging and discharging efficiency of the battery.
[0027] In a possible embodiment, the electrolyte further includes a third solvent, and the third solvent is at least configured to increase the coupling probability of the first solvent and the electrolyte salt; the mass proportion of the third solvent in the solvent mixture is greater than or equal to 40% and less than or equal to 80%.
[0028] In a possible embodiment, the third solvent includes diethyl carbonate (DEC).
[0029] Likewise, diethyl carbonate DEC can increase the coupling probability between the first solvent and the electrolyte salt, thereby increasing the conductivity of the electrolyte, reducing concentration polarization and improving the uniformity and efficiency of the electrolyte.
[0030] In a possible embodiment, the electrolyte further includes a film-forming additive, and the film-forming additive is at least configured to form a passivation film on the surface between the positive electrode and the electrolyte, and / or between the negative electrode and the electrolyte.
[0031] In a possible embodiment, the relative dielectric constant of the first solvent is greater than or equal to 60.
[0032] In a possible embodiment, the film-forming additive includes at least one of 1,3-propane sultone (PS), methylene disulfonate (MMDS), diethylene sulfate (DTD), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), and lithium difluorobis(oxalatophosphate) (LiDFOP).
[0033] In a possible embodiment, the mass proportion of the film-forming additive in the electrolyte is in the range of 3%-10%.
[0034] On the other hand, a secondary battery is provided, comprising: a positive electrode plate, a separator, a negative electrode plate; and the above-mentioned electrolyte; the electrolyte comprises a film-forming additive, and the film-forming additive is used to form a passivation film between the electrolyte and the positive electrode plate, and / or to form a passivation film between the electrolyte and the negative electrode plate.
[0035] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application, and do not constitute improper limitations on the present application.
[0037] Figure 1 A charging curve diagram of a battery electrolyte before and after polymerization according to some embodiments;
[0038] Figure 2 The figure is a discharge curve diagram of a battery electrolyte before and after polymerization according to some embodiments. DETAILED DESCRIPTION
[0039] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.
[0040] Unless the context requires otherwise, throughout the specification and claims, the term "including" is to be interpreted as an open, inclusive meaning, that is, "including, but not limited to". In the description of the specification, the terms "one embodiment", "some embodiments", "exemplary embodiments", "examples" or "some examples" and the like are intended to indicate that specific features, structures, materials or characteristics associated with the embodiment or example are included in at least one embodiment or example of the present disclosure. The schematic representations of the above terms do not necessarily refer to the same embodiment or example. In addition, the specific features, structures, materials or characteristics described may be included in any one or more embodiments or examples in any appropriate manner.
[0041] In the following, the terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present disclosure, unless otherwise specified, "plurality" means two or more.
[0042] “At least one of A, B, and C” has the same meaning as “at least one of A, B, or C” and both include the following combinations of A, B, and C: A only, B only, C only, the combination of A and B, the combination of A and C, the combination of B and C, and the combination of A, B, and C.
[0043] “A and / or B” includes the following three combinations: A only, B only, and a combination of A and B.
[0044] The use of "for" or "configured to" herein is intended to be open and inclusive language that does not exclude devices being for or configured to perform additional tasks or steps.
[0045] According to some embodiments of the present disclosure, a secondary battery is provided, which may also be called a rechargeable battery or storage battery. It is a battery that can restore its charge through a reverse electrochemical reaction for repeated use. In the present disclosure, the secondary battery may be simply referred to as a battery.
[0046] According to the different materials of the positive electrode, secondary batteries can be divided into lithium cobalt oxide batteries, lithium manganese oxide batteries, lithium iron phosphate batteries, etc. According to different types, secondary batteries can be divided into battery cells, battery modules or battery packs, etc.
[0047] Exemplarily, the battery includes a positive electrode plate, a separator, a negative electrode plate and an electrolyte, wherein the electrolyte includes an electrolyte salt, an initiator and a solvent mixture, and the mass proportion of the solvent mixture in the electrolyte ranges from 70% to 80%.
[0048] Exemplarily, the mass proportion of the solvent mixture in the electrolyte may be 70%, 72%, 74%, 76%, 78% or 80%, etc.
[0049] The solvent mixture includes a first solvent and a second solvent. The first solvent is configured to undergo a polymerization reaction under the action of an initiator to form an electrolyte gel when the temperature of the electrolyte is greater than or equal to the temperature of the electrolyte. The second solvent is configured to improve the flame retardant properties of the electrolyte. The mass proportion of the first solvent in the solvent mixture is 15%-35%.
[0050] For example, the mass proportion of the first solvent in the solvent mixture may be 15%, 20%, 25%, 30% or 35%.
[0051] When the temperature of the electrolyte or battery is greater than the threshold temperature, the first solvent and the initiator self-polymerize to form a gel electrolyte, which can effectively reduce the side reaction of the electrolyte with the positive electrode and / or the negative electrode, thereby reducing the heat generated by the side reaction of the electrolyte. In addition, the gel electrolyte formed by self-polymerization increases its impedance and significantly reduces its conductivity, which, on the one hand, suppresses the short circuit in the battery or battery cell, and on the other hand, isolates the electronic conduction between the positive electrode and the negative electrode, effectively reducing the heat generated by the short circuit in the battery or battery cell.
[0052] In addition, at the operating temperature of the battery or battery cell, the electrolyte is in liquid form, retaining the electrochemical properties of conventional liquid electrolytes. Compared with solid electrolytes and gel electrolytes, the electrolyte provided by the embodiments of the present disclosure has better interface compatibility and higher lithium ion conductivity.
[0053] Therefore, the electrolyte provided by the embodiments of the present disclosure has both the electrochemical properties of a liquid electrolyte and the safety properties of a gel electrolyte.
[0054] In some possible embodiments, the threshold temperature is greater than or equal to 80 degrees Celsius.
[0055] For example, the threshold temperature may be 80 degrees Celsius, 81 degrees Celsius, or 82 degrees Celsius, etc.
[0056] Setting the threshold temperature to 80 degrees Celsius can, on the one hand, prevent the polymerization temperature from being too low and causing adverse effects on the operating temperature range of the battery. On the other hand, in the electrolyte provided by the embodiment of the present disclosure, some solvents have a low boiling point, for example, the boiling point is between 80 degrees Celsius and 110 degrees Celsius. If the threshold temperature is set too high, the electrolyte will boil before the first solvent and the initiator undergo a polymerization reaction, which can easily cause adverse effects on the polymerization reaction. Therefore, setting the threshold temperature at 80 degrees Celsius not only ensures the operating temperature of the battery, but also prevents the boiling of the solvent from affecting the polymerization reaction and thus affecting the safety of the battery.
[0057] In some possible embodiments, the first solvent may include a compound including an alkenyl group.
[0058] Exemplarily, the first solvent may include at least one of vinylene carbonate VC and vinyl ethylene carbonate VEC.
[0059] On the one hand, the relative dielectric constant of vinylene carbonate VC and vinyl ethylene carbonate VEC is relatively high, and the conductivity of the electrolyte prepared by using it as the first solvent is greater than or equal to 15mS / cm. On the other hand, vinylene carbonate VC and vinyl ethylene carbonate VEC also act as polymer monomers, and undergo polymerization reaction with the initiator when the battery or electrolyte reaches the threshold temperature, and the macromolecules formed by the self-polymerization of vinylene carbonate VC hardly react with the positive electrode or the negative electrode at high temperature, that is, there is almost no side reaction at the interface of the positive electrode and / or the negative electrode, which can well suppress the reaction heat generated by the electrolyte at the positive electrode and / or the negative electrode. In addition, vinylene carbonate VC has a good affinity for graphite and can form a dense film on the graphite surface.
[0060] Exemplarily, the relative dielectric constant of the first solvent is greater than or equal to 60. The higher the relative dielectric constant, the easier it is to combine with lithium ions to dissociate lithium salts, greatly improving the conductivity of the electrolyte, and thus improving the rate performance of the battery or battery cell.
[0061] In some possible embodiments, the initiator includes at least one of an azo compound and a peroxide.
[0062] Exemplarily, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.
[0063] In some feasible embodiments, the mass proportion of the initiator in the electrolyte is in the range of 0.1%-1%.
[0064] For example, the mass proportion of the initiator in the electrolyte may be 0.1%, 0.4%, 0.7% or 1%, etc.
[0065] The temperature at which the polymerization reaction between the first solvent and the initiator occurs can be changed by adjusting the ratio, amount and / or type of the initiator, that is, the threshold temperature of the electrolyte can be flexibly adjusted according to actual needs.
[0066] In some feasible embodiments, the mass proportion of the second solvent in the solvent mixture is greater than or equal to 10% and less than or equal to 30%.
[0067] For example, the mass proportion of the second solvent in the solvent mixture may be 10%, 15%, 20%, 25% or 30%.
[0068] The second solvent includes at least one of a fluorinated solvent and a phosphate ester solvent.
[0069] Exemplarily, the second solvent includes at least one of methyl trifluoroethyl carbonate FEMC, di(2,2,2-trifluoroethyl) carbonate TFE C, trimethyl phosphate TMP, triethyl phosphate TEP, tri(2,2,2-trifluoroethyl) phosphate TFP, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether D2, methyl perfluorobutyl ether MFE and 1,1,1,3,3,3-HFPM.
[0070] The second solvent provided in the embodiment of the present disclosure can effectively increase the coupling probability of lithium ions with vinylene carbonate VC and / or vinyl ethylene carbonate VEC, thereby increasing the dissociation ratio of the lithium salt.
[0071] In addition, methyl trifluoroethyl carbonate FEMC, di(2,2,2-trifluoroethyl) carbonate TFEC, and DEC have flame retardant and self-extinguishing properties. When the second solvent includes at least one of methyl trifluoroethyl carbonate FEMC, di(2,2,2-trifluoroethyl) carbonate TFEC and DEC, the safety characteristics of the electrolyte can also be improved. For example, when the electrolyte temperature is higher than the threshold temperature, vinylene carbonate VC and / or vinyl ethylene carbonate VEC reacts with the initiator to form a gel electrolyte, and methyl trifluoroethyl carbonate FEMC, di(2,2,2-trifluoroethyl) carbonate TFEC and / or DEC in the second solvent use their own flame retardant and self-extinguishing properties to prevent the electrolyte from burning and catching fire during the thermal runaway stage.
[0072] Exemplarily, methyl trifluoroethyl carbonate FEMC, di(2,2,2-trifluoroethyl) carbonate TFEC, and DEC also have good compatibility with graphite, thereby forming a dense and stable SEI film on the graphite surface.
[0073] In some feasible embodiments, the electrolyte salt includes at least one of lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium bis(trifluoromethylsulfonylimide) and lithium bis(fluorosulfonylimide). The concentration range of the electrolyte salt is 0.8 mol / L-2 mol / L, wherein mol / L means mole per liter.
[0074] For example, the concentration of the electrolyte salt may be 0.8 mol / L, 1.1 mol / L, 1.4 mol / L, 1.7 mol / L, or 2 mol / L.
[0075] Exemplarily, the mass proportion of the electrolyte salt in the electrolyte is 10%-18%, specifically 10%, 12%, 14%, 16% or 18%.
[0076] The electrolyte salts selected in the embodiments of the present disclosure are all high-temperature qualitative lithium salts, which have good thermal stability and chemical stability, can reduce the risk of electrolyte decomposition, and increase the cycle life of the battery. Their good thermal stability also enables the electrolyte to maintain good performance in low or high temperature environments, thereby allowing the battery to work stably under various environmental conditions. In addition, these lithium salts are not easy to decompose at high temperatures, which can reduce the risk of thermal runaway of the battery, thereby increasing the safety characteristics of the battery using the electrolyte provided by the embodiments of the present disclosure.
[0077] For example, most high-stability lithium salts, such as lithium bis(fluorosulfonyl)imide, have high ionic conductivity, which helps to improve the charge and discharge efficiency of the battery.
[0078] In some feasible embodiments, the electrolyte further includes a third solvent, and the third solvent is configured to increase the coupling probability between the first solvent and the electrolyte salt.
[0079] Exemplarily, the third solvent may be diethyl carbonate DEC.
[0080] The mass proportion of the third solvent in the solvent mixture is greater than or equal to 40% and less than or equal to 80%.
[0081] Illustratively, the mass proportion of the third solvent in the solvent mixture may be 40%, 50%, 60%, 70% or 80%.
[0082] Likewise, diethyl carbonate DEC can increase the coupling probability between the first solvent and the electrolyte salt, thereby increasing the conductivity of the electrolyte, reducing concentration polarization and improving the uniformity and efficiency of the electrolyte.
[0083] In some feasible embodiments, the electrolyte further includes a film-forming additive, and the film-forming additive is at least configured to form a passivation film on the surface between the positive electrode and the electrolyte, and / or between the negative electrode and the electrolyte.
[0084] Exemplarily, the film-forming additive may be at least one of PS, MMDS, DTD, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate).
[0085] In some feasible embodiments, the mass proportion of the film-forming additive in the electrolyte is in the range of 3%-10%.
[0086] For example, the mass proportion of the film-forming additive in the electrolyte may be 3%, 5%, 7% or 10%.
[0087] The film-forming additive can prevent excessive interfacial impedance caused by excessive reaction of vinylene carbonate VC and / or vinyl ethylene carbonate VEC at the interface of the positive and negative electrodes, thereby improving the electrochemical performance of the battery.
[0088] According to some embodiments of the present disclosure, a secondary battery is also provided, comprising a positive electrode plate, a separator, a negative electrode plate, and an electrolyte as described above. The electrolyte comprises a film-forming additive for forming a passivation film between the electrolyte and the positive electrode plate, and / or, forming a passivation film between the electrolyte and the negative electrode plate.
[0089] Exemplarily, the positive electrode material can be any one of ternary high voltage (cut-off voltage greater than or equal to 4.4V), high nickel material (nickel content greater than or equal to 80%, cut-off voltage greater than or equal to 4.4V), cobalt-free, lithium-rich manganese-based material, and lithium iron phosphate, and the negative electrode material includes at least one of graphite, silicon oxide or silicon nitrogen.
[0090] The following are examples of electrolytes provided according to the present disclosure, and comparative examples provided according to related technologies.
[0091] Comparative Example 1
[0092] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0093] The organic solvents ethylene carbonate and ethyl methyl carbonate are mixed uniformly in a volume ratio of 3:7;
[0094] Add 1.1 mol / L of electrolyte salt lithium hexafluorophosphate to the mixed solution;
[0095] Adding other functional additives VC2% and lithium difluorooxalate borate 0.5% to prepare an electrolyte;
[0096] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0097] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0098] Exemplarily, the main material of the positive electrode plate can be selected from high specific energy materials such as lithium-rich manganese-based and ternary high nickel, and the ternary high nickel material is, for example, a ternary high nickel Ni9 system or a ternary high nickel Ni8 system. The main material of the negative electrode plate can be selected from any one of artificial graphite, silicon-oxygen composite artificial graphite, or silicon-carbon composite artificial graphite. In other comparative examples or embodiments, the main materials of the positive electrode plate and the negative electrode plate can be the same as those in comparative example 1.
[0099] Comparative Example 2
[0100] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0101] The organic solvents ethylene carbonate, ethyl methyl carbonate and trifluoroethyl carbonate were uniformly mixed in a volume ratio of 3:4:3;
[0102] Add 1.1 mol / L of electrolyte salt lithium bis(fluorosulfonyl)imide to the mixed solution;
[0103] Adding other functional additives VC2% and lithium difluorooxalate borate 0.5% to prepare an electrolyte;
[0104] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0105] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0106] Comparative Example 3
[0107] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0108] The organic solvents ethylene carbonate, ethyl methyl carbonate and trifluoroethyl carbonate were uniformly mixed in a volume ratio of 3:4:3;
[0109] Add 1.1 mol / L of electrolyte salt lithium hexafluorophosphate to the mixed solution;
[0110] Adding other functional additives VC2% and lithium difluorooxalate borate 0.5% to prepare an electrolyte;
[0111] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0112] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0113] Comparative Example 4
[0114] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0115] The organic solvents ethylene carbonate, ethyl methyl carbonate and triethyl phosphate were uniformly mixed in a volume ratio of 3:4:3;
[0116] Add 1.1 mol / L of electrolyte salt lithium hexafluorophosphate to the mixed solution;
[0117] Adding other functional additives VC2% and lithium difluorooxalate borate 0.5% to prepare an electrolyte;
[0118] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0119] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0120] Example 1
[0121] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0122] Vinylene carbonate VC, methyl trifluoroethyl carbonate FEMC and triethyl phosphate TEP were mixed uniformly in a volume ratio of 3:5:2;
[0123] Add 1.0 mol / L of electrolyte salt lithium hexafluorophosphate to the mixed solution;
[0124] Add film-forming additives, 1.5% PS and 0.5% lithium difluorophosphate, to the mixed solution;
[0125] Adding an initiator and 0.5% azobisisobutyronitrile into the mixed solution to prepare an electrolyte;
[0126] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0127] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0128] Example 2
[0129] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0130] Vinylene carbonate VC, methyl trifluoroethyl carbonate FEMC and triethyl phosphate TEP were mixed uniformly in a volume ratio of 3:5:2;
[0131] Add 1.0 mol / L of electrolyte salt lithium bis(fluorosulfonyl)imide to the mixed solution;
[0132] Add film-forming additives, 1.5% PS and 0.5% lithium difluorophosphate, to the mixed solution;
[0133] Adding an initiator and 0.5% azobisisobutyronitrile into the mixed solution to prepare an electrolyte;
[0134] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0135] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0136] Example 3
[0137] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0138] Vinylene carbonate VC, methyl trifluoroethyl carbonate FEMC and triethyl phosphate TEP were mixed uniformly in a volume ratio of 3:5:2;
[0139] Adding electrolyte salt, 1.0 mol / L lithium bis(fluorosulfonyl)imide, and 0.2 mol / L lithium difluorooxalatoborate to the mixed solution;
[0140] Add film-forming additives, 1.5% PS and 0.5% lithium difluorophosphate, to the mixed solution;
[0141] An initiator, 0.1% of azobisisobutyronitrile, and 0.5% of benzoyl peroxide are added to the mixed solution to prepare an electrolyte;
[0142] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0143] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0144] Example 4
[0145] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0146] Vinylene carbonate VC, methyl trifluoroethyl carbonate FEMC and triethyl phosphate TEP were mixed uniformly in a volume ratio of 3:5:2;
[0147] Adding electrolyte salt, 1.0 mol / L lithium bis(fluorosulfonyl)imide, and 0.2 mol / L lithium difluorooxalatoborate to the mixed solution;
[0148] Add film-forming additives, 1.5% PS and 0.5% lithium difluorophosphate, to the mixed solution;
[0149] An initiator, 0.2% of azobisisobutyronitrile, and 0.8% of benzoyl peroxide are added to the mixed solution to prepare an electrolyte;
[0150] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0151] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0152] Example 5
[0153] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0154] Vinylene carbonate VC, methyl trifluoroethyl carbonate FEMC and triethyl phosphate TEP were mixed uniformly in a volume ratio of 5:3:2;
[0155] Adding electrolyte salt, 1.0 mol / L lithium bis(fluorosulfonyl)imide, and 0.2 mol / L lithium difluorooxalatoborate to the mixed solution;
[0156] Add film-forming additives, 1.5% PS and 0.5% lithium difluorophosphate, to the mixed solution;
[0157] An initiator, 0.1% of azobisisobutyronitrile, and 0.5% of benzoyl peroxide are added to the mixed solution to prepare an electrolyte;
[0158] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0159] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0160] Example 6
[0161] The preparation environment is an inert environment, such as an argon-filled glove box (H2O content ≤ 1 ppm);
[0162] Vinylene carbonate VC, methyl trifluoroethyl carbonate FEMC and triethyl phosphate TEP were mixed uniformly in a volume ratio of 5:3:2;
[0163] Adding electrolyte salt, 1.0 mol / L lithium bis(fluorosulfonyl)imide, and 0.2 mol / L lithium difluorooxalatoborate to the mixed solution;
[0164] Add film-forming additives, 1.5% PS and 0.5% lithium difluorophosphate, to the mixed solution;
[0165] An initiator, 0.2% of azobisisobutyronitrile, and 0.8% of benzoyl peroxide are added to the mixed solution to prepare an electrolyte;
[0166] The positive electrode sheet is prepared according to the ratio of main material: conductive carbon black: carbon nanotube: polyvinylidene fluoride = 96:1.4:0.4:2.2;
[0167] The negative electrode plate is prepared according to the main material: conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: styrene-butadiene rubber = 96:0.5:0.4:1.3:1.8.
[0168] The electrolytes and electrodes prepared in the above-mentioned comparative examples 1-4 and embodiments 1-6 were assembled into batteries for testing, and the test results shown in Table 1 were obtained, wherein the batteries in the comparative examples and the embodiments uniformly used soft-pack batteries, and the batteries mentioned in the present disclosure were, for example, selected from secondary batteries.
[0169] Table 1 High temperature cycle performance, high temperature storage, hot box performance and rate charging test results
[0170]
[0171] It can be seen from the test results in Table 1 that in the lithium ion batteries using the electrolytes of Examples 1-6, except for Example 1 having a conductivity of 8.12 mS / cm, the conductivity of Examples 2 to 6 is all above 9 mS / cm, the capacity retention rate of 1 coulomb and 1000 cycles at 45 degrees Celsius is all above 80%, and the highest can reach 83.51%, the residual capacity after continuous high-temperature storage at 85 degrees Celsius for 25 hours is all above 90%, and the highest can reach 94.87%, the step hot box combustion temperature is all above 185 degrees Celsius, and the highest can reach 230 degrees Celsius, and the pass rate of no combustion, no fire, and no explosion in the puncture test is all above 50%, among which the pass rate of Examples 4 and 5 is as high as 100%, which shows that the conductivity, high-temperature cycle performance, high-temperature storage performance, step thermal abuse performance, and puncture performance of the lithium ion batteries using the electrolytes of Examples 1-6 are all better than those of the lithium ion batteries using the electrolytes of Comparative Examples 1-4.
[0172] Moreover, in the lithium-ion batteries using the electrolytes of Examples 1-6, the constant current charging ratios are all around 80%, and the low-temperature discharge capacity at -20 degrees Celsius is approximately 81%-86%. It can be seen that the rate performance and low-temperature performance of the lithium-ion batteries using the electrolytes of Examples 1-6 are substantially at the same level as those of the lithium-ion batteries using the electrolytes of Comparative Examples 1-4.
[0173] It is easy to find out through analysis that lithium hexafluorophosphate is introduced into the electrolyte of comparative example 1, lithium bis(fluorosulfonyl)imide is introduced into the electrolyte of comparative example 2, trifluoroethyl carbonate is introduced into the electrolyte of comparative example 3, triethyl phosphate is introduced into the electrolyte of comparative example 4, and additives VC and lithium difluorooxalate borate are also partially introduced into comparative examples 1 to 4. However, except that the low-temperature discharge capacity of -20°C is basically the same as that of the embodiment, the other electrical properties or safety performances of the comparative examples are lower than those of the embodiment. This is mainly because the electrolyte of the comparative example only includes one or a few components of the embodiment, and it is impossible to form an electrolyte with multiple components like the electrolyte of the embodiment, and improve the electrical performance of the electrolyte to a certain extent while improving the safety performance of the electrolyte. For example, the triethyl phosphate / trifluoroethyl carbonate in the electrolyte of the comparative example can only prevent the electrolyte from being non-flammable, and it does not inhibit the combustible components produced by the side reactions of the electrolyte at the positive and negative electrode interfaces under high temperature conditions (including when the battery is thermally runaway), and thus does not have the safety performance of preventing thermal runaway of the electrolyte of the embodiment.
[0174] The electrolyte salt used in the electrolyte provided in the embodiment of the present disclosure has high-temperature stability, the solvent system is a non-flammable solvent, has flame retardant and self-extinguishing properties, and a high content of vinyl carbonate VC or vinyl ethylene carbonate VEC, a high-temperature initiator and some functional additives are combined into a functional electrolyte with high-temperature self-polymerization and flame retardant functions, so that the electrolyte can fully wet the positive and negative electrode interfaces under normal temperature conditions, so that it has the electrical properties of conventional electrolytes. At the same time, the film-forming additive forms a dense film on the surface of the positive and / or negative electrode plates, which can prevent the first solvent from reacting excessively at the positive and negative electrode interfaces, resulting in excessive interface impedance, that is, it can improve the electrochemical performance of the battery.
[0175] In addition, the electrolyte provided by the embodiments of the present disclosure also performs well in terms of safety characteristics. As shown in Table 1, the combustion temperature of lithium-ion batteries using the electrolytes of embodiments 1-6 in the step hot box test is above 185 degrees Celsius, and the highest temperature is 230 degrees Celsius. In the needle puncture test, the pass rate of no combustion, no fire, and no explosion is above 50%, and the highest temperature is 100%.
[0176] Among them, the film-forming additive PS decomposes under high pressure near the surface of the positive electrode to generate substances containing sulfite ions and lithium carbonate, etc. These products have a good isolation effect and are used to reduce the contact between the positive electrode and the electrolyte. Therefore, they have a good positive electrode film-forming protection effect, thereby improving the high-voltage cycle characteristics of the battery using the electrolyte provided by the embodiment of the present disclosure.
[0177] After the lithium difluorooxalatoborate is introduced as a film-forming additive, a redox reaction occurs on the surface of the positive and negative electrodes to generate a SEI (solid electrolyte interphase) film / CEI (Cathode-Electrolyte Interface) film rich in lithium fluoride, making it dense, thin, and highly thermally stable, thereby improving the electrochemical stability of the electrolyte system provided in the embodiments of the present disclosure to a certain extent.
[0178] By comparing Examples 1-6 with Comparative Examples 1-4, it can be found that due to the introduction of vinylene carbonate VC and initiators azobisisobutyronitrile and benzoyl peroxide, the electrolyte provided by the embodiments of the present disclosure has a self-polymerization effect under high temperature conditions. When the temperature is greater than or equal to the threshold temperature, for example, the temperature is greater than or equal to 80 degrees Celsius, the polymer gel electrolyte formed by vinylene carbonate VC and the initiator can isolate the side reactions of the electrolyte on the positive and negative electrode surfaces at high temperatures, thereby inhibiting the high-temperature thermal runaway of the battery cell. In addition, the conductivity of the polymer gel formed by the polymerization of vinylene carbonate VC and the initiator is significantly lower than that of the liquid electrolyte, which in turn increases the short-circuit impedance in the battery cell to a certain extent, and can further slow down the accumulation of heat in the battery cell under thermal runaway conditions, thereby effectively improving the safety performance of the battery cell.
[0179] For example, see Figure 1 and Figure 2 , Figure 1 is a charging curve diagram of a battery electrolyte before and after polymerization according to some embodiments, Figure 2 The figure is a discharge curve diagram of a battery electrolyte before and after polymerization according to some embodiments.
[0180] exist Figure 1 In the figure, the horizontal axis is capacity in ampere-hours, the vertical axis is voltage in volts, the dotted line represents the charging curve before the battery electrolyte is polymerized, and the solid line represents the charging curve after the battery electrolyte is polymerized.
[0181] exist Figure 2 In the figure, the horizontal axis is capacity in ampere-hours, the vertical axis is voltage in volts, the dotted line represents the discharge curve before the battery electrolyte is polymerized, and the solid line represents the discharge curve after the battery electrolyte is polymerized.
[0182] Depend on Figure 1 and Figure 2 It can be found that for a battery using the electrolyte provided by the embodiment of the present disclosure, the impact on the battery charging performance after the electrolyte is polymerized is a decrease in conductivity, and the impact on the discharge performance is a slight decrease in discharge capacity, which can be ignored.
[0183] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto, and any changes or substitutions within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. An electrolyte, characterized in that: include: Electrolyte salts; Initiator; A solvent mixture, wherein the electrolyte salt is dissolved in the solvent mixture; the solvent mixture comprises: The first solvent is at least configured to: generate a polymerization reaction under the action of the initiator when the temperature of the electrolyte is greater than or equal to a threshold temperature; a second solvent configured at least to improve the flame retardancy of the electrolyte; The mass proportion of the solvent mixture in the electrolyte is in the range of 70%-80%, and the mass proportion of the first solvent in the solvent mixture is greater than or equal to 15% and less than or equal to 35%.
2. The electrolyte according to claim 1, characterized in that The threshold temperature is greater than or equal to 80 degrees Celsius.
3. The electrolyte according to claim 1, characterized in that The first solvent includes a compound including an alkenyl group.
4. The electrolyte according to claim 3, characterized in that The first solvent includes at least one of vinylene carbonate and vinyl ethylene carbonate.
5. The electrolyte according to claim 1, characterized in that The initiator includes at least one of an azo compound and a peroxide.
6. The electrolyte according to claim 5, characterized in that The initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, di-tert-butyl peroxide and tert-butyl perbenzoate.
7. The electrolyte according to claim 1, characterized in that The mass proportion of the initiator in the electrolyte is in the range of 0.1%-1%.
8. The electrolyte according to claim 1, characterized in that The mass proportion of the second solvent in the solvent mixture is greater than or equal to 10% and less than or equal to 30%; The second solvent includes at least one of a fluorinated solvent and a phosphate ester solvent.
9. The electrolyte according to claim 1, characterized in that The second solvent includes at least one of methyl trifluoroethyl carbonate, di(2,2,2-trifluoroethyl) carbonate, trimethyl phosphate, triethyl phosphate, tri(2,2,2-trifluoroethyl) phosphate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, methyl perfluorobutyl ether, and 1,1,1,3,3,3-hexafluoroisopropyl methyl ether.
10. The electrolyte according to claim 1, characterized in that The electrolyte salt accounts for 10%-18% by mass in the electrolyte.
11. The electrolyte according to claim 1, characterized in that The electrolyte salt includes at least one of lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate, lithium bistrifluoromethylsulfonyl imide, and lithium bisfluorosulfonyl imide.
12. The electrolyte according to claim 1, characterized in that The concentration of the electrolyte salt in the electrolyte solution is in the range of 0.8 mol / L to 2 mol / L.
13. The electrolyte according to claim 1, characterized in that Also comprising a third solvent, the third solvent being configured at least to increase the coupling probability between the first solvent and the electrolyte salt; The mass proportion of the third solvent in the solvent mixture is greater than or equal to 40% and less than or equal to 80%.
14. The electrolyte according to claim 13, characterized in that The third solvent includes diethyl carbonate.
15. The electrolyte according to claim 1, characterized in that It also includes a film-forming additive, which is configured to form a passivation film on the surface between the positive electrode and the electrolyte, and / or between the negative electrode and the electrolyte.
16. The electrolyte according to claim 1, characterized in that The relative dielectric constant of the first solvent is greater than or equal to 60.
17. The electrolyte according to claim 15, characterized in that The film-forming additive includes at least one of 1,3-propane sultone, methylene disulfonate, vinyl sulfate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate).
18. The electrolyte according to claim 15, characterized in that The mass proportion of the film-forming additive in the electrolyte is in the range of 3%-10%.
19. A secondary battery, characterized in that: include: Positive electrode sheet, diaphragm, negative electrode sheet; as well as, The electrolyte according to any one of claims 1 to 18; The electrolyte includes a film-forming additive, and the film-forming additive is used to form a passivation film between the electrolyte and the positive electrode plate, and / or to form a passivation film between the electrolyte and the negative electrode plate.
Citation Information
Cited By
Battery and electric equipment thereof
CN122202511A
